Effectiveness of partially soluble photosensitizer in photodynamic microbiological inactivation: A curcumin example - Pratavieira, Sebastião; Matroodi, Fatima; Pinto-Júnior, Fabio Francisco; Rastelli, Alessandra Nara Souza; Bagnato, Vanderlei S.; Guimarães, Francisco E.G. (SPIE, the international society for optics and photonics, 2017)
We show that partial solubility of a photosensitizer is not necessarily a bad property when dealing with microbiological control. The presence of curcumin aggregates in solution may present advantages with respect the photo and chemical stability.